A Study to Assess the Level of Burden and Coping Strategies among Caregivers of Patient with Affective Disorders at Selected Hospitals of Sangli, Miraj, Kupwad Corporation Area (Indian Journal of Public Health Research & Development, 2020)
Introduction Interactions with caregivers of patients with severe mental illness like schizophrenia and bipolar affective disorder have revealed negative feelings about the disability status of their relative and burden related to caring for their relative with mental illness. Many caregivers have expressed that the patient‘s disability status affects the family pattern, roles of family members, prosperity of the family and relationship among the family members. Patient outcome and compliance with treatment are also dependent on optimal care giving and addressing family‘s needs. Unfortunately these needs are not routinely considered, addressed or met. Addressing the burden perceived by caregiver and improving their coping can assist with good clinical care of patients with severe mental illness and hence these study to assess the burden perceived by caregiver and their coping.1 Objectives: To assess the levels of Burden among care givers of patients with affective disorders and To assess the coping strategies among the caregivers of patients with affective disorders. Materials and Method: The researcher used quantitative research approach to assess burden and coping strategies. The research design was descriptive research design. The tool reliability coefficient ‘r’ of the scale was 0.7, hence it was found reliable. Total 120 samples were selected by non Probability convenient sampling technique. Total two scale namely Zarit burden interview and Rating scale for assessing coping strategies to collect data. The conceptual framework adopted is Sr.Calista Roy’s adaptation model (1984) the main concept of this conceptual framework is human being, stimuli, adaptation models and nursing. Results and Conclusion: In this study found the level burden among the care givers of affective disorders patients have experienced 60(50%)were had moderate to severe level of burden,29(24.17%) were had severe burden, 13(10.83) were had no or little burden and 18(15%) were had mild to moderate burden and levels of coping strategies among care givers, 19(15.83%) were had moderately adequate coping strategies, 93(77.50%) were had adequate coping strategies and 08(6.67%) were had inadequate coping strategies.
Keywords: : Care giver, Burden, Coping strategies